2019
DOI: 10.3354/dao03323
|View full text |Cite
|
Sign up to set email alerts
|

Novel dolphin morbillivirus (DMV) outbreak among Mediterranean striped dolphins Stenella coeruleoalba in Italian waters

Abstract: An unusual mortality event (UME) of striped dolphins Stenella coeruleoalba occurred in the period July to December 2016 along the Italian Ionian coastline. We conducted a complete postmortem examination on 28 specimens and detected dolphin morbillivirus (DMV), by means of biomolecular analyses, in the target tissues of 17 animals. Unlike previous outbreaks occurring in the Mediterranean Sea in 2011 and 2013, we observed typical pathological changes suggestive of morbilliviral infection in an acute/subacute pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 22 publications
2
24
0
Order By: Relevance
“…Under the "one health" framework, a wider perspective of CeMV is becoming more and more important, due to its progressively expanding host range in the Mediterranean Sea. As previously described, morbilliviruses are prone to host species jumps, like CeMV infecting several species of marine mammals, of canine distemper virus, able to infect non-human primates 32,34 . In conclusion, genomic information on the DMV strain of Cetacean morbillivirus are essential to understand its evolution as well as to infer its spatio-temporal trends also in the past, since the only available information relies on stranded animals.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Under the "one health" framework, a wider perspective of CeMV is becoming more and more important, due to its progressively expanding host range in the Mediterranean Sea. As previously described, morbilliviruses are prone to host species jumps, like CeMV infecting several species of marine mammals, of canine distemper virus, able to infect non-human primates 32,34 . In conclusion, genomic information on the DMV strain of Cetacean morbillivirus are essential to understand its evolution as well as to infer its spatio-temporal trends also in the past, since the only available information relies on stranded animals.…”
Section: Discussionmentioning
confidence: 70%
“…An hypothesis may be that the NE-Atlantic strain was introduced in the Mediterranean Sea in 2014 by the www.nature.com/scientificreports/ Strait of Gibraltar, known to be an area of contact between cetaceans from the two seas. The pod that was found stranded on the Adriatic shores of Italy 3,30,31 may have come into contact with a carrier pod from the Atlantic Ocean 32 . Either Globicephala melas and Stenella coeruleoalba may have introduced of the NE-Atlantic strain to the naive cetacean population of the Mediterranean Sea, due to their well documented roles as DMV carriers 8,33 .…”
Section: Discussionmentioning
confidence: 98%
“…The extent of shared habitat and foraging resources between striped and common dolphins would also have an effect on potential exposure to diseases, such as the cetacean or dolphin morbillivirus epizootics that have caused high mortality in odontocetes in Europe, the USA, and Australia (Van Bressem, Van Waerebeek, Jepson, et al, 2001; Van Bressem et al, 2014) and have affected striped dolphins in the Mediterranean (Aguilar & Raga, 1993; Raga et al, 2008) and common dolphins in the Black Sea since the 1990s (Birkun et al, 1999). Novel morbillivirus outbreaks are also being reported to affect striped dolphins in recent years (Mira et al, 2019; Pautasso et al, 2019). It has recently been reported that such cetacean morbillivirus has an increased tendency to cross ‘interspecies barriers’ (Jo, Osterhaus, & Ludlow, 2018), while having an immunosuppressive effect on dolphins becoming predisposed to other infections as well (Keck et al, 2010).…”
Section: Threatsmentioning
confidence: 99%
“…Genomic studies on DMV sequences circulating in the Mediterranean basin in the last 30 years show that the strain is generally well conserved [ 9 , 10 ]. In the last 6 years, however, the DMV Mediterranean strain has been substituted by a new variant called DMV northeast (NE)-Atlantic strain originating from the coasts of Galicia and Portugal [ 10 , 11 , 12 ]. No difference in virulence and disease severity between the two strains has been confirmed to date [ 4 ].…”
Section: Introductionmentioning
confidence: 99%